Peran Manajemen Risiko dan Perilaku Organisasi untuk Meningkatkan Kinerja (Studi pada Bank Umum Swasta Nasional & Persero) - Anton Baroto Budi Susatyo; Eka Afnan Troena; Armanu Thoyib; Ubud Salim (Jurnal Aplikasi Manajemen, 2012)
The aim of this research is to analyze how risk management implementation and organizational behavior, may simultaneously affect the organizational performance of banking organizations in Indonesia. Samples in this research are 99 commercial banks, including 5 national commercial banks, 68 private commercial banks, and 26 regional development banks. Data were collected using written questionnaires to all 99 commercial banks. At the end of the collection period, 81 responses (90% response rate) were obtained. After data eligibility verification, 76 commercial banks (84.4%) met the requirements for further analysis. All data were analyzed by Structural Equation Modeling (SEM). All four of relationship hypotheses are significantly proven. Analysis on organizational behavior and risk management indicate that the structure and process group indicator, and the strategic risk indicator, have the most influential effects to build their values respectively. As result, formation of the organizational behavior and the risk management implementation should be executed simultaneously to increase bank’s organizational performance. The bank’s risk management officers should prioritize the incurrence of interactions among organization elements and individuals on implementing risk management within the banking industry. Bank’s leaders should also build accurate plan on identifying, measuring, supervising, and managing each risk of the commercial bank activities, so that it may cope with bank’s turbulence to environment factors.Keywords: Risk Management, Organizational Behavior, Organizational Performance, Banking Industry.